Ladja: Luta para dançar - Monteiro, Edu (Revista Concinnitas, 2019)
Através de duas pesquisas distintas, separadas por um hiato de oitenta anos, o artigo investiga as transformações decorrentes do processo de ocidentalização na ladja – uma dança de combate embalada pelo canto e o toque do tambor, nascida nas encruzilhadas da diáspora africana na Martinica. Palavras-chave: Ladja. Dança de combate. Diáspora africana. Arte na Martinica. Abstract Through two different researches, separated by a gap of eighty years, the article investigates the transformations resulting from the process of westernization in the ladja – a combat dance performed by the chant and the drumming, born at the crossroads of the African diaspora in Martinique. Keywords: Ladja. Combat dance. African diaspora. Art in Martinique.